Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Di Ling-Ling’s Restaurant Seminyak - Anggreni, Ni Luh Dian; Widiantara, I Gusti Agung Bagus; Poetranto, Isa Wahjoedi Dwi (Universitas Triatma Mulya, 2024)
This study aims to determine whether there is an influence between work discipline and work motivation as an independent variable on employee performance as a dependent variable. The author uses data collection techniques with documentation, observation and surveys. The number of respondents sampled in this study was 64 employees. The results of the descriptive analysis include the average employee age of 18-25 years where more female employees with an average education level of diploma and an average length of work of 1-5 years. The methods used are multiple linear regression analysis, determination analysis and beta coefficient analysis which are processed with the SPSS (statistical package for the social science) program version 26. The results of the analysis for work discipline (x1) obtained a t-count of 3.145 stated that there was a positive and significant influence on employee performance (y) and for work motivation (x2) obtained t-count of 3.535 stated that there was a positive and significant influence on employee performance (y). In simultaneous processing, f-count is obtained from both variables that have a positive and significant influence with a value of 27.765. Based on the large coefficient of determination, the percentage value of work discipline and work motivation on employee performance is 47.7% with the more dominant variable being work motivation.